Dampak Gadget Terhadap Perilaku Alone Together - Amalia Rosyadi Putri (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2022)
This article discusses the role of the device or gadget, which is the latest communication tool that must be owned by each individual in the new media era. Everyone's daily life is spent with gadgets that are equipped with all the features. It can answer every modern human need. Thus, gadgets have a significant impact, one of which is the attitude of being alone together. This research is a qualitative research that will reveal the impact of gadgets on the attitude of being alone together which indicates social and moral decadence. The results of this study indicate that gadgets have reduced social values ​​in which people communicate verbally and nonverbally. Social reality (not virtual reality) is the most important thing in building values ​​in society, but with this gadget telecommunication system, people are increasingly trapped in virtual reality. The construction of the alone together attitude is an attitude of unconsciousness where this is a form of abnormality, because what is called normality are those who can communicate face-to-face. This does not necessarily erase the presence of gadgets with all their positive impacts, but society must be able to balance the progress of the times with intelligent minds and religious points of view as well as religiosity and values ​​that are equally appropriate and also fill each individual's personal space.